The application of One Health concept to an outdoor problem-based learning activity for veterinary students - Tengku Azizan, Tengku Rinalfi Putra; Mohd Noor, Mohd Hezmee; Bachek, Noor Farhana; Abu Hassim, Hasliza; Abdul Razak, Intan Shameha; Idris, Lokman Hakim; Ahmad, Yusof Hamali; Salisi, Mohd Shahrom; Abdul Ghani, Ahmad Afifi; Shahudin, Muhammad Syafiq; Qayyum, M. A. L.; Ahmad, Hafandi; et al. (Veterinary World, 2016)
Background: The One Health (OH) approach, which seeks to bring together human and animal health, is particularly suited to the effective management of zoonotic diseases across both sectors. To overcome professional silos, OH needs to be taught at the undergraduate level. Here, we describe a problem-based learning activity using the OH approach that was conducted outdoors for 3rd-year veterinary students in Malaysia. Materials and Methods: A total of 118 students, divided into two groups, completed the activity which spanned 1½ days at a deer park adjacent to a wilderness area. Students were asked to evaluate the activity using an online survey that had quantitative and qualitative components. Results: Response rate was 69.5%. The activity was rated excellent by 69.5% and good by 30.4%. Levels of satisfaction were high on a range of criteria. 97.5% of students intended to take action in their studies as a result of what they had learned. Conclusions: Delivery of an outdoor problem-based learning activity using OH approach was very successful in terms of participation, knowledge delivery and understanding, and the willingness of students to integrate OH into their future practice. For the improvement of future programs, the involvement of other disciplines (such as Medical, Biology, Biotechnology, Biomedical, and Public Health) is being considered.